Complicated multi-drug resistant typhoid fever with cerebral oedema, diffuse encephalitis, and fungal infection of the oral cavity—a case report - Raza, Muhammad Umar; Shakeel, Nimra; Waqar, Syed Hamza Bin; Ramsha Shakeel; Zaidi, Syed Muhammad Hussain (Journal of the Pakistan Medical Association, 2023)
Enteric fever is a highly fatal infectious disease that can present with extensive symptoms that renders diagnosis quite risky. Multi-drug resistant Salmonella typhi infection has become endemic in third world countries and has been routinely associated with catastrophic complications and even death, with diagnostic and therapeutic impedance. Typhoid fever is known to cause life-threatening cerebral complications. We report the case of a 16-year-old male who presented to us with a high-grade fever, watery diarrhoea, altered level of consciousness, and a mixed dark-coloured crusted oral lesion. Blood workup showed neutropenia, lymphocytopenia, thrombocytopenia, transaminitis, and hyponatraemia. Blood culture grew multi-drug resistant Salmonella Typhi. CT scan of the brain showed diffuse cerebral oedema, while EEG was consistent with the diagnosis of diffuse encephalitis. The patient responded well to culture-sensitive antibiotics, while the oral lesion showed a dramatic response to presumptive antifungal treatment. ---Continue